Efecto de cinco Densidades de siembra en la fase de engorde del Camarón Gigante (Macrobrachium rosenbergii), en el Trópico seco de San Martin-Perú - Ruíz Sánchez, María Emilia (2001)
In this study, we present the observations and results of our research carried out between May and September 1 999. We tried out tour stocking densities in the fatting phase of the giant prawn of Malaysia (Macrobrachium rosenbergil) in the enterprise “Camaronera del Oriente - CORSA' situated on the right banks of the Cumbaza River, in the district Morales. Province San Martín, region San Martín, Perú. The stocking densities we evaluated were: treatment T1 (4 prawns / m"), treatment T2 (6 prawns / m"), treatment T3 (7 prawns / m"), treatment T4 (7,5 prawns / m2), and a witness which is treatment TO with 5 prawns ! m2 (the density used by CORSA). The total gain of weight in each treatment was: 34.55 grams for TO, 37.81 grams for T1, 31 .60 grams for T2, 30.95 grams for T3 and 33.32 grams for T4 in this, T1 indicated a significant difference in comparison with the other treatments. The average daily growth of weight was: 0.2998 grams for T0, 0.3262 grams for T1, 0.2767 grams for T2, 0.0.2704 grams for T3 and 0.2877 grams for T4. In this, T1 indicated a significant difference in comparison with the other treatments. The total gain of size in each treatment was: 9.97 cm for T0, 10.88 cm for T1, 8.80 cm for T2, 8.43 cm for T3 and 8.84 cm for T4. In this, T1 indicated a significant difference in comparison with the other treatments. The average daily growth was 0.083 cm for TO, 0.091 cm for T1, 0.073 cm for T2, 0.070 cm for T3 and 0.074 cm for T4. In this, T1 indicated a significant difference in comparison with the other treatments. The mortality - loss in each treatment was: 21 .70% for TO, 11.30% for T1, 22.70% for T2. 24.10% for T3 and 28.60% far T4 in this T1 indicated the lowest mortality rate with regard to the other treatments. The commercial production expressed in percentages was: 63.73% far TO, 69.55% far T1, 69.66% for T2, 57.52% for T3 and 57.25% for T4. In this, T1 and T2 indicated a significant difference in comparison with the other treatments. The profitability rates after the realization of a benefit - costs analysis for each treatment were: 48.78% for TO, 53.79% for T1, 71 .30% for T2, 46.59% for T3 and 44. 75% for T 4. In this, T2 (6 prawns/ m2) indicated, in comparison with the other treatments the highest profitability rate which is 71.30%.